2020
DOI: 10.24269/ijhs.v4i2.2641
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Tingkat Stres Akademik Pada Mahasiswa Stikes Graha Medika

Abstract: Salah satu masalah kesehatan terbesar yang memiliki dampak pada kinerja akademik adalah masalah stres akademik. Mahasiswa menjadi kelompok yang rentan terhadap stres yang berasal dari kehidupan akademik. Stres yang biasanya dialami mahasiswa disebabkan adanya tuntutan kehidupan dan tanggung jawab akademik. Perubahan sistem pembelajaran online selama pandemi Covid-19 mengharuskan mahasiswa memperoleh tugas yang lebih banyak dan jadwal perkuliahan yang padat. Penelitian ini menggunakan design cross sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
1
1
0
3
Order By: Relevance
“…The results of the analysis of demographic data with academic stress showed that more were found in the high category at the ages of 18 and 19. This is in line with previous research, which states that age has a relationship with academic stress (Hamzah & Hamzah, 2020). It is also made clear in other studies that age and number of visits to the hospital have a relationship with academic stress (Suwartika et al, 2014).…”
Section: B Demographics and Academic Stress Factorssupporting
confidence: 92%
“…The results of the analysis of demographic data with academic stress showed that more were found in the high category at the ages of 18 and 19. This is in line with previous research, which states that age has a relationship with academic stress (Hamzah & Hamzah, 2020). It is also made clear in other studies that age and number of visits to the hospital have a relationship with academic stress (Suwartika et al, 2014).…”
Section: B Demographics and Academic Stress Factorssupporting
confidence: 92%
“…For freshmen, various demands from the academy are sources of heavy stress (Amirkhan & Kofman, 2018). The online learning process during pandemics has become one of the main sources of stress, caused by a lot of workloads, sub-optimal explanations, and feedback processes providing by teachers (Argaheni, 2020;Hamzah & Hamzah, 2020;Hasanah et al, 2020;Livana et al, 2020: Sundarasen al., 2020. Other stressors in a pandemic are loneliness and social isolation (Elmer et al, 2020;Hwang, Rabheru, Peisah, Reichman, & Ikeda, 2020), which are related to peer relations, either it is in the context of friendship or romantic relationships (Anderson, Salk, & Hyde, 2015;Seiffge-Krenke et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, dilansir dari lama kompas.com, hasil penelitian yang dilakukan oleh tim psikologi UI menunjukkan bahwa mahasiswa cenderung memiliki emosi ke arah yang negatif yang dapat mempengaruhi kondisi kesehatan mentalnya. Stres akademik dapat diartikan sebagai tekanan mental yang berkaitan dengan frustasi terhadap kegagalan akademik, ketakutan akan kegagalan tersebut bahkan kesadaran terhadap kemungkinan terjadinya kegagalan tersebut (B & Hamzah, 2020). Salu (2017) menggambarkan stres akademik sebagai suatu keadaan dimana terjadi ketidaksesuaian antara tuntutan lingkungan dengan sumber daya aktual atau kemampuan yang dimiliki siswa sehingga mereka semakin terbebani oleh berbagai tekanan dan tuntutan.…”
Section: Pendahuluanunclassified